The use of hair as an indicator of occupational 14C contamination - Stenström, Kristina; Unkel, Ingmar; Nilsson, Carl Magnus; Rääf, Christopher; Mattsson, Sören (Radiation and environmental biophysics, 2010)
This paper presents a study in which the specific activity of 14C in hair has been investigated as an easily determined bio-indicator of the integrated 14C exposure (over several months). The study includes 28 Swedish workers handling 14C-labelled compounds, or working in a 14C-enriched environment. Hair samples from personnel at a Swedish nuclear power plant showed very low levels of 14C contamination, if any. In contrast, personnel at the investigated research departments showed 14C levels in hair of up to 60% above the natural specific activity of 14C. Much higher levels, up to 80 times the natural specific activity of 14C, were found in hair from individuals working at a pharmaceutical research laboratory. This contamination was, however, not solely an internal contamination. There were indications that most of the 14C in the hair originated from airborne 14C-compounds, which were adsorbed onto the hair. The difficulties in removing this external 14C contamination prior to analysis are discussed, as are the possibilities of using accelerator mass spectrometry to analyse various types of samples for retrospective dose assessment.
Im Titel ist 14 hochgestellt
Online veröffentlicht: 25. September 2009
Gesehen am 19.02.2025